Diazapentacenes from Quinacridones - Wiesner, Thomas; Ahrens, Lukas; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Chemistry - a European journal, 2021)
Bis(silylethynylated) 5,7- and 5,12-diazapentacenes were synthesized from cis- and trans-quinacridone using protection, alkynylation and deoxygenation. The solid-state packing of the targets is determined by choice and position of the silylethynyl substituents. The position of the substituents and nitrogen atoms influence the optical properties of the targets.
First published: 08 December 2020
Gesehen am 17.04.2023